FAKTOR YANG MEMPENGARUHI DISIPLIN DIRI PADA ANAK USIA 4-5 TAHUN DI TK LASKAR PELANGI KABUPATEN KUBU RAYA - Maisyarah, Maisyarah; Fadillah, Fadillah; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract      Factors Affecting Self-Discipline of Children 4-5 Years Old at Laskar Pelangi Kindergarten, Kubu Raya Regency. This study aims to: (1) find out the internal factors that affect self-discipline of children aged 4-5 years in Laskar Pelangi Kindergarten, Kubu Raya Regency, (2) find out external factors influence self-discipline of children aged 4-5 years, (3) find out the dominant factors that influence self-discipline of children. This study uses the description method. Data collection in this study uses direct observation, direct communication and documentary methods. The analysis technique used is descriptive statistical analysis. The results show that (1) internal factors that influence self-discipline of children aged 4-5 years in Laskar Pelangi Kindergarten, Kubu Raya Regency are parenting, children who get democratic parenting tend to be disciplined children while children who get authoritarian parenting and permissive tend to be undisciplined children, (2) external factors that influence self-discipline of children are education and income of parents, children who have parents with higher education tend to be children of discipline and children from middle-income parents tend to be disciplined children, (3) the dominant factor affecting self-discipline of children is parenting style. Keywords: Early Childhood, Internal Factors, External Factors, Dominant Factors, Disipline